1. GENOMIC BIOMARKERS IN ENDOMETRIAL CARCINOMA (Iraqi Journal of Medical Sciences, 2019)
Endometrial carcinoma is the second most common gynecological cancer in developing countries after cervical carcinoma and its incidence is increasing due to the rise in the rate of obesity. Diagnosis depend on invasive test (biopsy) with no routine screening investigation available for either general population or high-risk group, there are several types of biomarkers that can be used for diagnosis, prognosis and management but none are available for routine clinical practice. Following the discovery of the new gene-based classifications of endometrial cancer, the use of these gene-based biomarkers will be the cornerstone in the early diagnosis and management for endometrial carcinoma patients in the coming years.Keywords:Endometrial carcinoma, screening, PTEN, miRNA, P53, circulating tumor DNA, genomic classificationCitation:Kareem NM. Genomic biomarkers in endometrial carcinoma. Iraqi JMS. 2019; 17(2): 100-102. doi: 10.22578/IJMS.17.2.1
Keywords: Endometrial carcinoma; screening; PTEN; miRNA; P53; circulating tumor DNA; genomic classification